When Job Earnings Are Behind Poverty Reduction - Inchauste, Gabriela (World Bank, Washington, DC, 2014)
Improvement in labor market conditions has been the main explanation behind many of the poverty success stories observed in the last decade, that is the primary conclusion of an analysis of changes in poverty by income source. Changes in labor earnings were the largest contributor to poverty reduction for a sample of 16 countries where poverty increased substantially. In 10 of these countries, labor income explained more than half of the change in poverty, and in another 4 countries, it accounted for more than 40 percent of the reduction in poverty. A declining dependency rate accounts for over a fifth of the reduction in poverty in 10 out of 16 countries, while transfers and other non-earned incomes account for more than a quarter of the reduction in poverty in 9 of these countries. A further decomposition of the contribution of labor income to poverty reduction in Bangladesh, Peru, and Thailand found that changes in individual characteristics (education, work experience, and region of residence) were important, but that overall, increases in real earnings among the poor matter the most.